2010
DOI: 10.1111/j.1399-3038.2010.01046.x
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of allergic rhinitis in childhood

Abstract: The distinction between 'seasonal' and 'perennial' allergic rhinitis (AR) is not always adequate. The 'Allergic Rhinitis and its Impact on Asthma' (ARIA) work group suggested a new classification for AR based on severity and duration of symptoms. Our primary aim was to describe the natural history and burden of AR according to the new ARIA criteria in a population-based birth cohort study of children up to 13 yr. We defined symptoms as 'severe' (impairment of daily activities) or 'mild' (no impairment) and 'pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
82
2
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(96 citation statements)
references
References 23 publications
5
82
2
7
Order By: Relevance
“…The proportion of children with allergic rhinitis increased from 5.4% to 14.0% from age 4 to 8 years; these findings are consistent with those from other longitudinal studies. 3,4 The proportion of children with nonallergic rhinitis decreased slightly, from 8.1% to 6.3%, during the same period. This should be considered in light of the fact that the prevalence of rhinitis, in general, increased from age 4 to 8 years, from 14% to 20%.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The proportion of children with allergic rhinitis increased from 5.4% to 14.0% from age 4 to 8 years; these findings are consistent with those from other longitudinal studies. 3,4 The proportion of children with nonallergic rhinitis decreased slightly, from 8.1% to 6.3%, during the same period. This should be considered in light of the fact that the prevalence of rhinitis, in general, increased from age 4 to 8 years, from 14% to 20%.…”
Section: Discussionmentioning
confidence: 90%
“…There is some evidence that the incidence of allergic rhinitis increases with age. [2][3][4] Allergic rhinitis has been defined as symptoms of sneezing and nasal itching, with obstruction and mucosal discharge, caused by an IgE-mediated reaction. 1 However, few longitudinal studies have used the combination of symptoms of rhinitis and an objective measure for IgE in the definition of pediatric allergic rhinitis.…”
mentioning
confidence: 99%
“…There was a male predominance of allergic rhinitis and female predominance of nonallergic rhinitis during adolescence. The MAS study followed up 467 children until 13 years and showed similar frequency of rhinitis (20). Allergic rhinitis, but not nonallergic rhinitis, in early childhood is a risk factor for developing asthma in later childhood (21) and adulthood (22).…”
Section: Prevalence and Epidemiologymentioning
confidence: 97%
“…4,6 It typically begins in childhood or adolescence and mostly seems to affect children between 6 and 14 years of age 6 ; nevertheless, the prevalence in adulthood is high, ranging from 12% in Spain to 46% in Australia. 7 In Germany Keil et al 8 found the 12-month prevalence of AR at 6 years of age to be substantially lower (12%) than that at 13 years of age (30%) in the Multicentre Allergy Study birth cohort. The prevalence of ever having physician-diagnosed AR in 6-year-old schoolchildren has been increasing, from 1.3% to 3.2% in eastern Germany and from 2.5% to 3.2% in western Germany.…”
mentioning
confidence: 99%